Electrospray Mediated Localized and Targeted Chemotherapy in a Mouse Model of Lung Cancer - Ruzgys, Paulius; Böhringer, Stephan; Dokumaci, Ayse Sila; Hari, Yvonne; Schürch, Christian M.; Brühl, Frido; Schürch, Stefan; Szidat, Sönke; Riether, Carsten; Šatkauskas, Saulius; Geiser, Thomas; Hradetzky, David; et al. (Frontiers in Pharmacology, 2021)
Background: Advanced stage, centrally localized invasive tumor is major cause of sudden death in lung cancer patients. Currently chemotherapy, radiotherapy, laser ablation or surgical resection if possible are available state of art treatment but none of these guarantee remedy or a long term relief and are associated with fatal complications. Direct and localized drug delivery to the tumor that allows localized chemotherapy could be a promising option for preoperative down staging or palliative therapy. Here we report localized and targeted application of intra tumor delivery of chemotherapy using a novel device based on the principle of electrospray. Methods: C57BL/6J mice were injected with 2x106 Lewis lung carcinoma cells subcutaneously. After 15 days, the animals were anesthetized and the tumors were exposed after skin incision. Tumors were electrosprayed with 100 µg cisplatin on days 0 and 2, and tumor volumes were measured daily. Animals were sacrificed at day 7 after first electrospray and tumors were analyzed by immunohistochemistry. Results: In this proof of concept study, we report that tumor volume was reduced by 81.2 % (22.46 mm3 ± 12.14 mm3) after two electrospray mediated Cisplatin delivery while control tumor growth at same time point increased by 200 % (514.30 mm3 ± 104.50 mm3). Moreover, Caspase positive cells were increased after Cisplatin electrospray compared to other groups of animals. Conclusion: Targeted drug delivery by electrospray is efficient in the subcutaneous mouse model of lung cancer and offers a promising opportunity for further development towards clinical application.